Estudio de tiempos y movimientos para el proceso de producción de hidróxido de calcio en la empresa PROCALSACOM – Riobamba - Santillán Santos, Erik Andrés (2026)
This research project was carried out at PROCALSACOM, a company that was experiencing problems with low productivity, lack of control, and a lack of standardization in its production process. Given this situation, the objective was to optimize calcium hydroxide production by applying a time and motion study to increase productivity. The research took a quantitative, field-based, documentary approach at a descriptive level. Direct observation techniques were used to analyze the process, along with industrial engineering tools such as the two-handed diagram, SIPOC, 5M analysis, and prioritization matrix, identifying the grinding stage as the main bottleneck. After evaluating the current method, an improvement proposal was designed by applying various study methods. It was found that the original method produced 200 bags in 35.81 hours (5.59 bags/hour), while the proposed method allows 220 bags to be produced in 33.27 hours (6.61 bags/hour), achieving an overall improvement of 18.18%. As a result, time reductions were achieved in key activities, increasing productivity per hour of work, obtaining 720 bags per month, and increasing performance in the production process.